2020
DOI: 10.1097/jxx.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and perceptions of nurse practitioners about antibiotic stewardship

Abstract: Background: Antibiotic stewardship (ABS) is a set of strategies to optimize the use of antibiotics with the goal of reducing antibiotic resistance, improving patient outcomes and decreasing unnecessary costs. ABS affects all venues of patient care, including outpatient, inpatient, and long-term care. While many strategies for ABS exist and best practice continues to evolve, successful ABS programs utilize a multidisciplinary approach. Nurse practitioners (NPs) play an essential role in health care education an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…It is important that prescribers understand the wider implications of AMR on patient outcomes. The positive results in the knowledge test correlate with earlier studies; in the United States, Hamilton et al found that 97% ( n = 194) of nurse practitioners understood antibiotics can harm the patient and inappropriate use can cause resistance (97%) [ 11 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is important that prescribers understand the wider implications of AMR on patient outcomes. The positive results in the knowledge test correlate with earlier studies; in the United States, Hamilton et al found that 97% ( n = 194) of nurse practitioners understood antibiotics can harm the patient and inappropriate use can cause resistance (97%) [ 11 ].…”
Section: Discussionsupporting
confidence: 69%
“…Evidence also exists for a subset of medical prescribers and nurses. Earlier studies have reported good knowledge of antibiotics among nurse practitioners and their intention to prescribe antibiotics appropriately [ 11 , 12 ]. Factors impacting nurse and physician prescribing have included patient pressure, fear, complacency and time [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…207 infection preventionists (IPs) working in acute care hospitals (1) Leadership support of nurses’ involvement in antibiotic stewardship; (2) Nurses’ performance in antibiotic stewardship activities; (3) Nurses’ knowledge and training in antibiotic stewardship The survey consisted of 40 multiple-choice and free-text questions Study findings indicate the need for nurse leaders to improve the preparation and integration of clinical nurses in ASPs. While clinical nurses routinely perform activities that contribute to optimal antibiotic use, the knowledge and competency of clinical nurses in these activities and their formal integration in ASPs are minimal Hamilton et al [ 22 ] Utah (USA) Cross-sectional study The 2018 annual American Association of Nurse Practitioners (AANP) conference in Denver, Colorado Describe the knowledge, attitudes, and perceptions of NPs about antibiotic use, resistance, and stewardship NPs. 194 NPs completed the questionnaire.…”
Section: Data Extractionmentioning
confidence: 99%
“…Although studies and public health campaigns that investigate and target the general public's knowledge and understanding of antibiotics and antibiotic resistance have been conducted [7,8], and there is some evidence for medical prescribers and nurses, a gap remains in the literature regarding multidisciplinary HCW's knowledge, attitudes and behaviours on this topic [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%